Considering User Feedback and Consistency, Analysis of the level of User Satisfaction with Particular reference to MIMER Medical College, Pune - Dolai, Bidhan; Shenmare, Sanjay (Nepal Journal of Multidisciplinary Research, 2022)
The primary means of ensuring that everyone has reliable, safe, and equal access to information are libraries. It serves as a community hub for ongoing knowledge dissemination. It serves as a catalyst for propriety and is a significant indicator of a mature society. This essay looks at the MIMER Medical College Central Library's user experience and service excellence. Quantitative student opinions on the library's offerings were gathered through survey techniques. 54 replies from UG students were gathered (MBBS). Using spss software, the reliability test (cronbach's alpha) was performed on the data. This study's goal is to evaluate usability and reliability. the most crucial research stage, provides the researcher with the theoretical underpinnings of a study problem.